Efficacy of gamification-based smartphone application for weight loss in overweight and obese adolescents: study protocol for a phase II randomized controlled trial. (June 2018) - Timpel, Patrick; Cesena, Fernando Henpin Yue; da Silva Costa, Christiane; Soldatelli, Matheus Dorigatti; Gois, Emanuel; Castrillon, Eduardo; Díaz, Lina Johana Jaime; Repetto, Gabriela M.; Hagos, Fanah; Castillo Yermenos, Raul E.; Pacheco-Barrios, Kevin; Musallam, Wafaa; et al.
Background: Overweight and obesity are significant public health concerns that are prevalent in younger age cohorts. Preventive or therapeutic interventions are difficult to implement and maintain over time. On the other hand, the majority of adolescents in the United States have a smartphone, representing a huge potential for innovative digitized interventions, such as weight loss programs delivered via smartphone applications. Although the number of available smartphone applications is increasing, evidence for their effectiveness in weight loss is insufficient. Therefore, the proposed study aims to assess the efficacy of a gamification-based smartphone application for weight loss in overweight and obese adolescents. The trial is designed to be a phase II, single-centre, two-arm, triple-blinded, randomized controlled trial (RCT) with a duration of 6 months. Method: The intervention consists of a smartphone application that provides both tracking and gamification elements, while the control arm consists of an identically designed application solely with tracking features of health information. The proposed trial will be conducted in an urban primary care clinic of an academic centre in the United States of America, with expertise in the management of overweight and obese adolescents. Eligible adolescents will be followed for 6 months. Changes in body mass index z score from baseline to 6 months will be the primary outcome. Secondary objectives will explore the effects of the gamification-based application on adherence, as well as anthropometric, metabolic and behavioural changes. A required sample size of 108 participants (54 participants per group) was calculated. Discussion: The benefits of the proposed study include mid-term effects in weight reduction for overweight and obese adolescents. The current proposal will contribute to fill a gap in the literature on the mid-term effects of gamification-based interventions to control weight in adolescents. This trial is a well-designed RCT that is in line with the Consolidated Standards of Reporting Trials statement.